Castings practice the 10 rules of castings - Campbell, John, 1938- (Elsevier/Butterworth-Heinemann, 2004)
Each chapter of Professor Cambell's new book Castings Practice will take a look at one of his 10 rules. It is to be expected that the Rules wil one day be taken as an outline or blueprint for an international specification on the methods for making reliable castings. John Cambell has over two decades of experience in the casting industry and is the author of over 40 technical papers and patents. He has become well-known in the foundry industry as the originator of the Cosworth casting process, which is becoming accepted throughout the world as a new production process for the casting of cylinder heads and blocks. He is now Federal Mogul Professor of Casting Technology at the University of Birmingham.
Revised edition of: Castings. Oxford : Butterworth-Heinemann, 1991.
Keywords: Founding.; Metal castings.; elektronické knihy; electronic books